2011
DOI: 10.1111/j.1365-246x.2011.05151.x
|View full text |Cite
|
Sign up to set email alerts
|

Rupture process of the 2001 May 7 Mw 4.3 Ekofisk induced earthquake

Abstract: S U M M A R YOn 2001 May 7, following unintentional water injection, a moderate size induced earthquake struck the Ekofisk oil field, North Sea. Despite of its relatively moderate magnitude, clear low-frequency waveforms could be recorded up to more than 2000 km epicentral distance, suggesting a slow rupture at very shallow depth and wave propagation through low-velocity shallow structures. The event poses a rare opportunity to constrain rupture velocity, duration and rise time of a superficial M > 4 event occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Especially the near‐field GPS data with observed uplift could demonstrate, in combination with the retrieved source mechanism, that the seismic source centroid was shallow above the field formation at the eastern border of the field [ Cesca et al , ]. A kinematic inversion for parameters of the extended source and rupture further indicated that the subhorizontal plane ruptured unilaterally over a length of about 6 km in azimuthal direction of about 133° [ Cesca et al , ]. The kinematic solution further indicated a very slow rupture velocity of only about 500 m s −1 (equal to 0.26 times the shear wave velocity) and a long rise time of about 7 s. The unusual slow and long rupture explains that such a moderate‐strong earthquake was able to radiate energetic low‐frequency Rayleigh and Love waves well observed up to 2000 km epicentral distance.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially the near‐field GPS data with observed uplift could demonstrate, in combination with the retrieved source mechanism, that the seismic source centroid was shallow above the field formation at the eastern border of the field [ Cesca et al , ]. A kinematic inversion for parameters of the extended source and rupture further indicated that the subhorizontal plane ruptured unilaterally over a length of about 6 km in azimuthal direction of about 133° [ Cesca et al , ]. The kinematic solution further indicated a very slow rupture velocity of only about 500 m s −1 (equal to 0.26 times the shear wave velocity) and a long rise time of about 7 s. The unusual slow and long rupture explains that such a moderate‐strong earthquake was able to radiate energetic low‐frequency Rayleigh and Love waves well observed up to 2000 km epicentral distance.…”
Section: Applicationsmentioning
confidence: 99%
“…The kinematic solution further indicated a very slow rupture velocity of only about 500 m s −1 (equal to 0.26 times the shear wave velocity) and a long rise time of about 7 s. The unusual slow and long rupture explains that such a moderate‐strong earthquake was able to radiate energetic low‐frequency Rayleigh and Love waves well observed up to 2000 km epicentral distance. As suggested by Ottemöller et al [] and supported by the kinematic source inversion of Cesca et al [], the rupture was likely to be triggered by an unintended water injection during about 2 years of 1.9·10 6 m 3 in 2 km depth near the northern central part of the field [ Ottemöller et al , ] (see Figure a for location). The triggering of the earthquake rupture may have been realized by the formation and slow growth of a large horizontal hydrofracture within the overburden in about 2 km depth within the shale and mud rocks.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even a low‐aftershock productivity evidenced, e.g., by Dahm et al [] for an induced earthquake in Germany, in comparison to tectonic earthquake of similar magnitude in the same region, could be finally linked to the shallow source location within different geological units. Still linked to shallow depth and near‐surface processes, Cesca et al [] found anomalous slow rupture of about 500 m/s for an induced earthquake, taking place along a weakened shallow subhorizontal failure plane, at the Ekofisk gas field, North Sea. Recently, Folesky et al [] studied the rupture directivity of fluid‐induced microseismic events and analyzed the induced seismicity sequence related to the EDS project in Basel (Switzerland).…”
Section: Challenges In Discriminating Induced/triggered From Natural mentioning
confidence: 99%
“…In mining environments, the analysis of microseismicity is important for mines stability monitoring (e.g., Cesca, Sen, & Dahm, 2014;Gharti, Oye, Roth, & Kuehn, 2010;Sen, Cesca, Bischoff, Meier, & Dahm, 2013). In particular, different human operations, including mining (e.g., Bischoff, Cete, Fritschen, & Meier, 2010;Feignier & Young, 1992;Fletcher & McGarr, 2005;McGarr, 1992;Sen et al, 2013;Trifu, Angus, & Shumila, 2000), water reservoirs impoundment (Do Nascimento, Lunn, & Cowie, 2005;Gough & Gough, 1970;Guha, 2000;Gupta & Rastogi, 1976), wastewater or fluid injection also including brine from hydraulic fracturing of shales (Ake, Mahrer, O'Connell, & Block, 2005;Cornet & Jianmin, 1995;Ellsworth, 2013;Healy, Rubey, Griggs, & Raleigh, 1968;Kim, 2013;Sasaki, 1998;Sileny, Hill, Eisner, & Cornet, 2009;Tadokoro, Ando, & Nishigami, 2000), geothermal fields operation (e.g., Deichmann & Giardini, 2009;Brodsky & Lajoie, 2013;Ross et al, 1999), and oil and gas field exploitation (e.g., Bardainne, Dubos-Sallée, Sénéchal, Gaillot, & Perroud, 2008;Cesca, Dahm, Juretzek, & K€ uhn, 2011;Dahm et al, 2007;Grasso & Wittlinger, 1990;Rutledge, Phillip, & Schuessler, 1998) and gas injection (Cesca et al, in press) can trigger or induce seismicity. Modern full waveform analysis methods can significantly contribute to monitor and understand the dynamics of rupturing processes and the perturbation to the background stress field, for example, in order to detect weakened regions and evaluate risks of further dangerous ruptures or chan...…”
Section: Introductionmentioning
confidence: 99%